2020
DOI: 10.21815/jde.019.160
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Sectional Study of Empathy Among Dental Students at King Abdulaziz University

Abstract: Empathy is the fundamental substructure of moral behavior. Skillful clinicians may not necessarily be successful dentists if they do not have sufficient empathy. The aim of this study was to assess the level of empathy among dental students at King Abdulaziz University with an emphasis on the effect of gender and study level. A cross‐sectional study was carried out among third‐ to sixth‐year dental students of King Abdulaziz University in Jeddah, Saudi Arabia. A validated, self‐administered Jefferson Scale of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
4
14
1
4
Order By: Relevance
“…Literature shows that Malaysian and Indian male dental students demonstrated higher mean empathy scores than female students [ 23 , 24 ]. However, consistent with previous research in dental students [ 10 , 15 , 18 , 20 ], females had significantly higher empathy scores than males in the current study. Similarly, in the majority of studies on medical and other health profession students, the higher empathy score was reported in females than males [ 2 , 12 , 13 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Literature shows that Malaysian and Indian male dental students demonstrated higher mean empathy scores than female students [ 23 , 24 ]. However, consistent with previous research in dental students [ 10 , 15 , 18 , 20 ], females had significantly higher empathy scores than males in the current study. Similarly, in the majority of studies on medical and other health profession students, the higher empathy score was reported in females than males [ 2 , 12 , 13 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the female gender, high GPA, and senior class years/internship were significantly related to high empathy in our sample. The mean empathy score in our study was 96.75 ± 13.76 which is higher than that reported in a recent study of Saudi dental students by Naguib et al in Jeddah who showed that the mean empathy score was 84.84 ± 11.28 [ 18 ]. Dental literature shows varying levels of empathy in dental students in different parts of the world.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The fifth and sixth year students had higher scores than the third and fourth year students although the differences were not statistically significant. 24 Furthermore, a study on Polish dental students showed an increase in empathy from the first and second to fourth years, where it reached its maximum. Levels decreased during the fifth year with students having to meet a set target to finish the course.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth and sixth year students had higher scores than the third and fourth year students although the differences were not statistically significant. 24 …”
Section: Discussionmentioning
confidence: 99%